Gingivoplasty with high-intensity diode laser for gingival enlargement - Muñoz Lara, Antonio Isaac (2020)
The article reports the case of a 53-year-old male patient, who went to the Clinic of University Dental Services (SERODU), in Ecuador, for presenting a gingival smile. He had no relevant medical history. He was diagnosed with a gingival enlargement of teeth 1.1, 1.2 and 2.1 and was treated with high intensity diode laser gingivoplasty. After 15 days of control, good healing was observed and the patient stated that he had no postoperative pain.The objective of this clinical case is to show the benefits of the high intensity diode laser, for the treatment of gingival enlargement and thereby achieve a better aesthetic perception of the upper anterior teeth.